Answer:
[tex]D=V*\sqrt{\frac{2H}{g} } -\frac{H}{4}[/tex]
Explanation:
From the vertical movement, we know that initial speed is 0, and initial height is H, so:
[tex]Y_{f}=Y_{o}-g*\frac{t^{2}}{2}[/tex]
[tex]0=H-g*\frac{t^{2}}{2}[/tex] solving for t:
[tex]t=\sqrt{\frac{2H}{g} }[/tex]
Now, from the horizontal movement, we know that initial speed is V and the acceleration is -g/4:
[tex]X_{f}=X_{o}+V*t+a*\frac{t^{2}}{2}[/tex] Replacing values:
[tex]D=V*\sqrt{\frac{2H}{g} }-\frac{g}{4}*\frac{1}{2} *(\sqrt{\frac{2H}{g} })^{2}[/tex]
Simplifying:
[tex]D=V*\sqrt{\frac{2H}{g} } -\frac{H}{4}[/tex]